2014
DOI: 10.1017/s1047951114000626
|View full text |Cite
|
Sign up to set email alerts
|

Absence of association of FCGR2A gene polymorphism rs1801274 with Kawasaki disease in Greek patients

Abstract: Kawasaki disease is an acute, febrile syndrome in infancy, characterised by vasculitis of medium-sized arteries, and affects predominantly young children. Family-based studies on Kawasaki disease supports the contribution of genetic factors in disorder manifestation. In a recent genome-wide association study, the polymorphism rs1801274 of FCGR2A [Fc fragment of immunoglobulin G, low-affinity IIa, receptor] gene has been implicated in disease pathogenesis. The aim of the present study was to explore the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Of note, SNPs (rs4810485 and rs1535045) within CD40 gene were associated with the development of KD in Taiwanese children (Kuo et al, 2012). Although literature has reported the possible genetic role of FCGR2A alleles for the pathophysiology of KD in Chinese children , other studies reported that there is no correlation between the SNP (rs1801274) of FCGRA2 gene and the incident of KD in patients of Greeks origin (Chatzikyriakidou et al, 2015;Qian et al, 2013). In Japan, while the number of CC chemokine ligand 3-like 1 gene copies is highly associated with the occurrence of KD and IVIG resistance, there were no correlation to the pathogenesis of KD in Korean patients (Kim et al, 2012a), suggesting the susceptibility genes for KD may be specific to ethnicity according to the results of GWAS.…”
Section: Candidate Genes and Genome-wide Association Studies Of Kdmentioning
confidence: 99%
“…Of note, SNPs (rs4810485 and rs1535045) within CD40 gene were associated with the development of KD in Taiwanese children (Kuo et al, 2012). Although literature has reported the possible genetic role of FCGR2A alleles for the pathophysiology of KD in Chinese children , other studies reported that there is no correlation between the SNP (rs1801274) of FCGRA2 gene and the incident of KD in patients of Greeks origin (Chatzikyriakidou et al, 2015;Qian et al, 2013). In Japan, while the number of CC chemokine ligand 3-like 1 gene copies is highly associated with the occurrence of KD and IVIG resistance, there were no correlation to the pathogenesis of KD in Korean patients (Kim et al, 2012a), suggesting the susceptibility genes for KD may be specific to ethnicity according to the results of GWAS.…”
Section: Candidate Genes and Genome-wide Association Studies Of Kdmentioning
confidence: 99%
“…Although the efforts to find a causative microorganism have failed [2][3][4] , the suspicion of an association between some unidentified microorganism and Kawasaki disease remains [4][5][6][7] . Investigations to identify a genetic susceptibility locus in Kawasaki disease also have been performed recently [8][9][10] . Several institutes had cooperated and reported a result regarding the genetic susceptibility of Kawasaki disease [11] .…”
Section: Introductionmentioning
confidence: 99%
“…During the fulltext screening, 14 more publications were further omitted for not conforming to our inclusion criteria. As a result, 11 eligible reports were ultimately encompassed into this meta- analysis [19][20][21][22][23][24][25][26][27][28][29], containing 17 independent studies. Of the studies, 13 were on Asian populations while only 4 on Caucasians.…”
Section: Yields Of Literature Searching and Selectionmentioning
confidence: 99%